Do trono à masmorra, um príncipe que não virou rei: uma análise jurídica da prisão cautelar e da colaboração premiada de marcelo odebrecht no âmbito da operação lava jato - Maia, Augusto de França (2020)
The Operation Lava Jato, the biggest initiative against corruption in the whole Brazilian history, has revealed a set of illegal practices perpetrated in several sectors of the State, mainly in State controlled companies - for example Petrobrás - involving politicians, civil servants, money changers and businessmen. The criminal organizations, charged of corruption, cartel formation, bid riggings and money laundering, carried out on a habitual and professional basis cartel practices which simulated a competitive situation in bidding procedures, whence those organizations profited enormously from overpriced contracts. In order to make it possible and perpetuate the crimes, they paid bribes and kickbacks to public office occupants with the help of money changers and transfers to bank accounts, mainly outside the country. Amongst the partakers in that scheme ranked some of the main political and business personalities in Brazil, like Marcelo Odebrecht, the heir and president of the biggest entrepreneurial group involved in that operation. After having been preventively taken into custody in Juny 2015, Marcelo Odebrecht came to an agreement with the Federal Prosecution Office and decided, in December 2016, to turn state's evidence. In this context, the present analysis deals with the legality of pre-trial detentions – based on the case of Marcelo Odebrecht and under the perspective of fundamental rights’ theory – and its effects on confession and state’s evidence. In order to accomplish that, this study must analyse the grounds of the judicial decisions which decreed the accused’s pre-trial detentions and if the agreement with the Federal Prosecution Office was influenced by the preventive detentions. Besides, the study will initially present the principal facts and features regarding the Operation Lava Jato, as well as the doctrinaire and jurisprudential grounds which conform the study of pre-trial detentions in Brazil. Lastly, the study will analyse the judicial decisions which have decreed the extreme preventive measures in order to conclude whether they are in accordance to the law, the jurisprudence and the legal doctrines. With indirect access to the proofs – once the survey draws mainly on the above-mentioned judicial decisions, especially due to the fact that the processes are still under judicial secrecy –, the analysis concluded that the arrest warrants meet the legal, jurisprudential and doctrinal criteria, whence it is possible to infer that the grounds of the preventive detention warrants of Marcelo Odebrecht were in accordance with the law, having been even confirmed by the superior courts. Therefore, one cannot consider, from the standpoint provided by the strict analysis of the decisions, that those warrants were issued in order to force the defendant to turn state’s evidence. The methodology employed here consisted in a broad bibliographical and documentary research through use of books, legislation in general, judicial decisions and press articles, which were all subjected to analysis and interpretation. The main conclusion drawn was that those pretrial detentions were decreed in due conformity with the laws